Bio-distribution and in vivo/in vitro toxicity profile of PEGylated polymer capsules encapsulating LaVO4:Tb3+ nanoparticles for bioimaging applications. Issue 60 (8th June 2016) - Dhanya, C. R.; Jeyaraman, Jaishree; Janeesh, P. A.; Shukla, Akansha; Sivakumar, Sri; Abraham, Annie
Abstract : Lanthanide-doped nanoparticles are being explored for bioimaging applications owing to their unique optical properties. Abstract : Lanthanide-doped nanoparticles are being explored for bioimaging applications owing to their unique optical properties. However, their toxicity profiles have not been explored in detail at the in vivo level which is a pre-requisite for clinical use. To this end, we have investigated a detailed in vivo / in vitro toxicity profiling of PEGylated polymer capsules encapsulating LaVO4 :Tb 3+ nanoparticles. First, in vitro toxicity studies were carried out in L929 mouse fibroblast cells in which MTT assay, neutral red uptake (NRU) assay, LDH release, cell morphology; quantification of reactive nitrogen species (RNS), reactive oxygen species (ROS), lipid peroxidation level, caspase-3 activity, and apoptosis assay were also performed. Second, in vivo studies were carried out in Swiss Albino mice, which included biodistribution studies (6 h and 24 h), evaluation of hematological parameters, and toxicity marker enzyme levels (inflammation, oxidative stress, tissue infiltration, liver dysfunction, etc. ), organ histology, and genotoxocity. The detailed investigation of toxicity at in vitro and in vivo levels indicates the biocompatibility of PEGylated polymer capsules encapsulating LaVO4 :Tb 3+ nanoparticles proving their suitability for bio-imaging applications.